Pilot Brewery and Malthouse I. F. B. M. - Jolibert, Franck (BrewingScience, 1997)
The ISO 9002 certification – for pilot brewing, malting and micromalting trials – allows I.F.B.M., the French brewing and malting institute, to lead investigations on the malting and brewing processes. Its Technological Studies department’s role and requirements are: development of barley evaluation programmes, malting and brewing courses, research and development, quality and performance improving.